Cognitive disability and the ethics of care : justifying dependency as a moral claim in relational justice - Maboloc, Christopher Ryan (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study seeks to explain the importance of the ethics of care in making society just and equal. It attempts to respond to the exclusion of persons with disability. Using the interpretive method, this paper asks about society’s ethical obligations to persons with cognitive disability. It argues that the idea of cash enhancement is not enough. Caring for persons with mental impairment requires the deep type of commitment that can only be founded in unconditional love and care. That justice is relational means that the child with autism requires the full attention of parents and the support of the state. But there is a gap since human society is reluctant to embrace the fact that there are persons who are dependent for life. The aim of this investigation is to argue that dependency on the part of individuals with cognitive disability is a morally justifiable claim that is rooted in the value of love and care as critical elements in the relational dimension of justice.